الديمقراطية تشاركية كألية لصنع القرار المحلي في الجزائر دراسة حالة بلدية الوادي 2016_2020 - زيد, راضية (جامعة الوادي university el-oued)
"تأتي هذه دراسة كمعالجة لإشكالية الديمقراطية التشاركية و صنع القرار المحلي في الجزائر دراسة حالة المجلس الشعبي اتضح لنا جليا أن الديمقراطية التشاركية كنظام حكم يمثل حاضنة لكل من المواطن والمجتمع المدني والقطاع الخاص و هذا في ضل منظومة قيمية يلتزم بها جميع الفواعل المشتركة في صنع القرار المحلي، وعدم التداخل في وظائفها، مع احترام القوانين والتشريعات والمساواة أمامها والمشاركة، والشفافية، كما أن البناء الديمقراطي التشاركي الحقيقي لابد أن يكون قائم على تأكيد سيادة الشعب وسلطته، وتعميق مفهوم المواطنة،وتحقيق العدالة الاجتماعية والتداول على السلطة. في هذا السياق، أوضحت لنا الدراسة واقع تطبيق الديمقراطية التشاركية على المستوى المحلي في الجزائر كما تمت في دراسة تسليط ضوء على بلدية الوادي كدراسة حالة الكلمات المفتاحية: الديمقراطية تشاركية. القرار المحلي. المشاركة. التدوال على سلطة. فواعل المتشركة. ""This study comes as a treatment for the problem of participatory democracy and local decision-making in Algeria as a case study The People’s Assembly, it became clear to us that participatory democracy as a system of government represents an incubator for both the citizen, civil society and the private sector, in light of a value system that all actors involved in local decision-making are committed to, and not overlapping in their functions, with respect for laws and legislation, equality before them, participation, and transparency, The real participatory democratic building must be based on affirming the people’s sovereignty and authority, deepening the concept of citizenship, achieving social justice and deliberating over power. In this context, the study explained to us the reality of the application of participatory democracy at the local level in Algeria, as was done in a study shedding light on the municipality of El-Oued as a case study. Keywords: participatory democracy. local decision. Share. Trade in power. doers of"
م.س.ع.21
Keywords: الديمقراطية تشاركية. القرار المحلي. المشاركة. التدوال على سلطة. فواعل المتشركة.; Participatory democracy. local decision. Share. Trade in power. joint verbs